Children’s Trilingual Songs (Indonesian, English, and Javanese) as Media for Strengthening the Diversity Character of Elementary School Students - Sinaga, Syahrul Syah (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2022)
Bhineka Tunggal Ika reflects national identity, which contains cultural diversity values in Indonesia. Issues of intolerance and globalization often found in Indonesia are the main reasons for instilling children’s character values about diversity through children’s trilingual songs. This study aims to create and develop children’s songs in three languages (trilingual), namely Indonesian, English, and Javanese, as an effort to strengthen children’s character about tolerance and diversity. This research is a type of research and development (RD) using the ASSURE model by combining qualitative and quantitative methods (mixed method). Data collection was carried out using the method of observation, interviews, and written input on the assessment sheet. Meanwhile, quantitative data is collected through questionnaires and assessment sheets in percentage values from experts and users. The results of the study show that the song “Harmony in Diversity” can be used as an educational medium in educating children to have a global outlook but still love the national language and preserve regional languages. This is because they have studied, expressed, and appreciated songs with trilingual meanings and lyrics. The children’s song “Harmoni dalam Keberagaman” is declared feasible and applicable for learning at the elementary school level. This is evidenced by the data validation results, which show that all indicators, namely song components, language, appearance, audiovisual media engineering, and implementation, get very feasible criteria, with an average score of 89.59%. The aspect that gets the highest score is the display aspect, with a score of 90.48%, and the aspect with the lowest percentage is the visual media design component and the song component, with a score of 87.5%..